PENGAWETAN LIMA BELAS JENIS KAYU SECARA RENDAMAN PANAS-DINGIN DENGAN BAHAN PENGAWET BFCA - Sasa Abdurrohim; Barly Barly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Wood samples of 15 species measuring 5 x 5 x 30 cm were treated with 5 percent of BFCA preservative by hot and cold soaking. Hot soaking period was respectiuely 1 hour, 3 houn and 5 hours, with temperature range of 65ᵒC - 70ᵒ C, followed by cold soaking for 24 hours. The test result of experiment, after taking both retention and penetration requirements into consideration for wood uses under roof, and in the open air both without ground contact, showed that nine Wood species could be satisfactorily treated under the experimental conditions. However, it is important to note that one of the nine species, i.e. benuang (Octomeles sumatrana) fulfilled the requirements for wood usage under the roof only without ground contact. The preservation schedule proposed for nine wood species is also presented in this paper.